Assessing research impact on poverty: the importance of farmers’ perspectives - Kristjanson, Patricia M.; Place, Frank; Franzel, Steven; Thornton, Philip K. (Elsevier, 2002)
In this paper we provide evidence to show that farmers' perspectives on poverty processes and outcomes are critical in the early stages of evaluating impact of agricultural research on poverty. We summarize lessons learned from farmer impact assessment workshops held in five African locations, covering three agro-ecological zones and five different agroforestry and livestock technologies arising from collaborative national–international agricultural research. Poverty alleviation is a process that needs to be understood before impact can be measured. Workshops such as those we describe can help researchers to identify farmers' different ways of managing and using a technology and likely effects, unanticipated impacts, major impacts to pursue in more quantitative studies, the primary links between agricultural technology and poverty, and key conditioning factors affecting adoption and impact that can be used to stratify samples in more formal analyses. Farmer workshops inform other qualitative and quantitative impact assessment methods. We discuss the linkage of farmer-derived information with GIS-based approaches that allow more complete specification of recommendation domains and broader-scale measurement of impact.